Nursing of a patient with diabetic peripheral vascular disease complicated with post-herpetic neuralgia (1例糖尿病性周围血管病合并带状疱疹后遗神经痛患者的护理体会) - SUN Lei (孙磊); WANG Cuiying (王翠英); ZHANG Xiangju (张香菊); SHEN Hui (申慧); ZHI Hui (智慧); WANG Yutao (王玉涛); TANG Ling (唐玲) (Association of Integrative Nursing, 2022)
This paper reviewed the analgesic treatment and nursing for a patient with diabetic peripheral vascular disease complicated with post-herpetic neuralgia. Based on the analgesic treatment, psychological nursing and health education and other intervention measures were carried out to relieve the clinical symptoms of disease and improve the treatment adherence of the patient. (本文回顾1例糖尿病性周围血管病合并带状疱疹后遗神经痛患者的镇痛治疗与护理经验。在配合完成镇痛治疗同时, 护理人员给予患者心理护理及健康宣教等干预措施, 提高患者依从性)